Evaluation of carboxylic, phosphonic, and sulfonic acid protogenic moieties on tunable poly(meta‐phenylene oxide) ionomer scaffolds. Issue 22 (4th October 2019) - Hudson, Reuben; Adhikari, Ramesh Y.; Tuominen, Mark T.; Hanzu, Ilie; Wilkening, Martin; Thayumanavan, Sankaran; Katz, Jeffrey L.
Abstract : A tunable, meta ‐linked aryl ether polymer scaffold enables the introduction of various acid groups for a fundamental comparison of their contributions to proton conduction. Sulfonic acid‐functionalized polymers offer the best proton conduction at low temperature and high relative humidity, while phosphonic acid‐functionalized polymers outperform sulfonic and carboxylic acid‐derived polymers at high temperature or low humidity.